Occurrence of fruit flies (Diptera: Tephritidae) in a mixed mango orchard in the city of Presidente Prudente, SP, Brazil - MARANGONI-MONTES, SÔNIA MARIA NALESSO; RAGA, ADALTON; DE SOUZA-FILHO, MIGUEL FRANCISCO (Revista Colombiana de Entomología, 2012)
The objective of this research was to determine the population dynamics and the diversity of fruit flies (Te phritidae) in a mixed orchard containing the mango (Mangifera indica) cultivars Haden, Tommy Atkins and Palmer, at the town of Presidente Prudente town, SP, Brazil. The population dynamics of fruit flies was measured from November 2005 to December 2007 through; weekly samplings of the adult insects, using yellow-bottomed McPhail traps baited with hydrolyzed protein. A total of 65,956 Tephritidae specimens was collected in nine traps, of which 2,788 were Anastrepha spp. (4.23%) and 63,168 Ceratitis capitata (95.77%). A total of 1,229 female specimens of Anastrepha was captured, of which 91.7% were A. obliqua, 3.3% A. fraterculus, 1.4% A. sororcula, 1.0% A. pseudoparalella and 0.7% A. striata. The remaining consisted of A. barbiellinii, A. daciformi, A. haywardi, A. zenildae, A. leptozona and A. montei. Ceratitis capitata and A. obliqua were the dominant species. In general, the highest densities of fruit flies occurred during the fruit-ripening period (from November to March), which is characterized by increased rainfall levels and high temperatures.